(untitled) (Academia Journal of Medicine, 2019)
Background: Rickettsiae along with their public health implications. They have addressed the co-circulation of differentspecies and genotypes of rickettsiae within the same endemic areas and how these observations may influence, correctly or incorrectly, the trends and conclusions drawn from the surveillance of rickettsial diseases in humans. Subjects and Methods: A total of 60 subjects, satisfying the inclusion and exclusion criteria were included in the final analysis. The sample size was calculated assuming the expected proportion of rickettsial infection as 11% among fever cases as per previously published studies, with a precision of 8% and 95% confidence level. Results: Among people with a tick bite, 3 (12.5%) people had 80 overall Weil-Felix titre. The number of people with 160, 320 and 640 overall Weil Felix titre was 4 (16.66%), 10 (41.66%) and 7 (29.16%) respectively in people with a tick bite. Among people without tick bite higher proportion of people had 80 and 160 titre. None of them had 640 titre. Statistical significant could not be tested due to zero number of subjects in one of the cells. Conclusion: Among people with pain abdomen 11 (23.91%) people had 80 Overall Weil-Felix titre. The number of people with 160, 320 and 640 Overall Weil Felix titre was 15 (32.60%), 13 (28.26%) and 7 (15.21%) respectively in people with pain abdomen. Among people without pain abdomen higher proportion of people had 80 and 160 titres. None of them had 320 and 640 titres. Statistical significant could not be tested due to zero number of subjects in one of the cells.